Uncertainty Assessment of Fuel Consumption Based on Open Data - Chevrot, Antoine; Basora, Luis (Journal of Open Aviation Science, 2023)
Accurate fuel consumption estimation is crucial for efficient aviation operations and fuel management. However, limited access to detailed traffic and aircraft performance data leads researchers to rely on open data sources for estimation, introducing uncertainties due to several assumptions. In this paper, we propose an uncertainty assessment of fuel-flow calculation using open data. By analyzing real-time flight data obtained from the OpenSky Network, comprising different aircraft types, we examine several commonly used hypotheses impacting fuel consumption. Variables such as flight altitude, airspeed, weight, or motorization are found to all contribute to variations in fuel consumption. Our goal is to perform a variance-based global sensitivity analysis to show the degree of impact of these variables on the final fuel consumption. This study highlights the significance of open data for refining fuel-flow estimation methodologies and provides researchers with a valuable resource seeking to improve fuel consumption calculations and develop more accurate models.